LASER-INDUCED TIME-RESOLVED LUMINESCENCE OF RARE-EARTH ELEMENTS IN SCHEELITE - Gaft M.; Panczer G.; Uspensky E.; Reisfeld R. (My University, 1999)
Natural and synthetic scheelite are investigated by time-resolved laser-induced luminescence to detect and ascribe various luminescence lines to a variety of REE. The selectivity of detection is possible by using different time delays after excitation, different gate widths and different excitation wavenumbers and allowed to detect REE in samples where they are hidden by intrinsic luminescence and not visible in the steady-state spectra as well as by cathodoluminescence. Luminescence of Pr3+, Er3+ and Tm3+ are detected even with low concentrations and in the presence of Tb3+, Dy3+ and Sm3+. Luminescence of Ho3+ and Yb3+ is firstly detected in natural scheelites and luminescence of Eu2+ and Ce3+ is preliminary suggested.